تحسين أداء الألواح الشمسية باستخدام عواكس مسطحة - جـــــــورج رامـــــي; صبيــــح مســـعود; عيسى إسماعيل (Latakia University Journal -Engineering Sciences Series, 2015)
يهدف هذا البحث إلى دراسة تأثير إضافة عواكس مسطحة إلى الألواح الشمسية الموجودة في كلية الهندسة الميكانيكية والكهربائية بجامعة تشرين من أجل تحديد زوايا ميلها الفضلى لتحسين أداء الألواح الشمسية خلال كامل ساعات النهار بزيادة كثافة الإشعاع الشمسي الساقط عليها. أظهرت نتائج البحث أن زاوية الميل الفضلى عن الشاقول للعاكس العلوي صيفاً هي 15° للخلف حيث حققت أعلى نسبة تحسن في القدرة الكهربائية للوح الشمسي مقدارها 13[%] بينما شتاءً كانت هذه الزاوية هي 10° للأمام والتي حققت أعلى نسبة تحسن ومقدارها 10.5[%]. وأظهرت نتائج البحث أن زاوية الميل الفضلى عن الأفق للعاكس السفلي صيفاً هي 35° حيث حصلنا على أعلى نسبة تحسن في القدرة الكهربائية للوح الشمسي مقدارها 17.5[%] بينما شتاءً كانت هذه الزاوية هي 10° والتي حققت أعلى نسبة تحسن ومقدارها 11.1[%]. وأظهرت نتائج البحث أيضاً أنه عند إضافة عاكسين معاً للوح الشمسي علوي وسفلي وفق زاويا الميل الموافقة حصلنا على نسبة تحسن في القدرة الكهربائية صيفاً مقدارها 20.3[%] وشتاء مقدارها 18[%]. The objective of this investigation is to study of influence of adding flat reflector to solar panels located at electrical and mechanical engineering faculty in Tishreen university to determine the optimum tilt angles of reflectors for improving the performance of solar panels during the whole day by increasing incident solar radiation intensity on solar panels. This investigation showed that the optimum tilt angle of upper reflector in summer is 15° backwards vertical where the improvement ratio in electrical power about 13[%] whereas in winter it is 10° towards vertical where the improvement ratio in electrical power about 10.5[%]. This investigation showed that the optimum tilt angle of down reflector in summer is 35° from horizontal where the improvement ratio in electrical power about 17.5[%] whereas in winter it is 10° from horizontal where the improvement ratio in electrical power about 11.1[%]. This investigation showed that using two reflectors together upper and down the solar panel with adequate tilt angles we get an improvement ratio in electrical power about 20.3[%] in summer and 18[%] in winter.